MENINGKATKAN HASIL BELAJAR SISWA KELAS II MENGGUNAKAN MEDIA GAMBAR MATEMATIKA DI UPTD SDN 1 TANJUNG INTEN - Betty Gusmia Dewi; Erni Mariana; Pixyoriza (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This research is motivated by the low learning outcomes of students in mathematics subjects of grade II at UPTD SDN 1 Tanjung Inten, especially in addition and subtraction materials, which is indicated by the majority of students not reaching the Learning Objective Completion Criteria (KKTP). The purpose of the research is to improve students' learning outcomes in mathematics subjects on addition and subtraction materials through the use of picture game media. The type of research used is Classroom Action Research (CAR) which is carried out in two cycles. Each cycle consists of planning, action implementation, observation, and reflection stages. The research subjects are 12 grade II students. Data collection techniques include learning outcome tests, student observation, and documentation. Data are analyzed descriptively quantitatively and qualitatively. The results of the study indicate that the use of picture media can improve students' learning outcomes. This is indicated by an increase in the percentage of learning completion from cycle I by 58.3%, increasing to 81.1% in cycle II. Thus, it can be concluded that the use of image media can improve learning outcomes in mathematics subjects on addition and subtraction for class II students at UPTD SDN 1 Tanjung Inten by 22.8%.